WORK DISCIPLINE SEBAGAI PEMEDIASI ETHICAL LEADERSHIP DAN DIGITAL WORK ENVIRONMENTTERHADAP EMPLOYEE PERFORMANCE - Ayu Trisna; Ananda Putri Raya; Tri Mulyani Kartini (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2025)
This research aims to provide empirical evidence about the influence of work discipline as a mediator of ethical leadership and the digital work environment on employee performance. The sample in this study were employees at PT Kilang Pertamina Internasional RU IV, with a sampling technique, namely purposive sampling. The number of respondents in this research was 158. This research is quantitative research using primary data obtained from distributing questionnaires to respondents. Proposing hypotheses in this research using the AMOS 24 software analysis tool. This research provides results that ethical leadership has a negative effect on employee performance, digital work environment has a positive effect on employee performance, ethical leadership has a positive effect on work discipline, digital work environment has a positive effect on work discipline, work discipline has a positive effect on employee performance, work discipline can mediate ethical leadership on employee performance, and work discipline can mediate the digital work environment on employee performance.